2006
DOI: 10.1515/epoly.2006.6.1.923
|View full text |Cite
|
Sign up to set email alerts
|

Atom transfer rearrangement radical polymerization of (2,4,6-trihalophenolato) Fe(II) / Ce(III) / Ce(IV) complexes in solid state

Abstract: The synthesis of poly(dihalophenylene oxide)s by thermal decomposition of Fe(II), Ce(III) and Ce(IV) phenolato complexes with pyridine as neutral ligands were achieved at different temperature ranges (140o - 250oC) with different time intervals (3 - 48 hr) via atom transfer rearrangement radical polymerization (ATRRP). The complexes were characterized by FTIR, DSC, UV-Visible, mass spectroscopy, magnetic susceptibility and elemental analyses. Structural analyses of polymers were performed by 1H and 13C-NMR, FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This mechanism was modified (4) in 1981 as a result of 13 C-NMR studies. The final proposal provided by Kısakürek et al (11,12) involves a similar mechanism which concludes the reaction to be atom transfer radical rearrangement polymerization.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…This mechanism was modified (4) in 1981 as a result of 13 C-NMR studies. The final proposal provided by Kısakürek et al (11,12) involves a similar mechanism which concludes the reaction to be atom transfer radical rearrangement polymerization.…”
Section: Introductionmentioning
confidence: 85%
“…Kısakürek et al (4,6,(8)(9)(10)(11)(12) revealed much progress in understanding the mechanism of the reaction.…”
Section: Introductionmentioning
confidence: 99%